Law, religion and the covenanted community: the impact of the Zurich Reformation on the early Cape settlement, 1652-1708 - A. W. G. Raath (Acta Theologica)
The Zurich Reformation was actively supported by the Dutch East India Company in its care for the religious, political and legal needs of the early Cape settlement. Not only the promotion of the Reformed religion by the Classis of Amsterdam but also the political and legal interests of the settlement were advanced on the basis of the Zurich reformation and its emphasis on the covenant. It was Huldrych Zwingli and his successor Heinrich Bullinger whose idea of the covenanted community served as the blueprint for the activities of the Sick Comforters, the proceedings of the Council of Justice and the decisions of the Council of Policy, rather than the influence of the Genevan reformer John Calvin. The so-called Calvinistic roots of the early settlement at the Cape, flowing from Calvin’s doctrine of predestination, must therefore, be thoroughly revisited.